(untitled) (Swiss Medical Weekly, 2017)
Bone targeted therapies are of increasing importance, not only for bone health in the clinical course of breast cancer, but recently also in the adjuvant setting as preventative, anticancer and prognosis-improving agents. It is well established that women with advanced breast cancer receive bisphosphonates or denosumab to prevent therapy-related osteoporosis. As many as 70% of these patients suffer from bone metastases and receive bone targeted agents in order to prevent skeletal related events (SREs), which are debilitating or diminish the quality of life. A number of trials provided guidance, identifying zoledronic acid as the most efficient bisphosphonate, showing that intravenous bisphosphonate administration is superior to oral intake and illustrating the different safety profile of denosumab, which has been reported to be more beneficial than zoledronic acid in delaying the time to first and subsequent (multiple) SREs. New studies have suggested that bone targeted therapies improve rates of overall survival and contribute to preventing recurrence of breast cancer at all sites. Increased bone turnover is both a consequence and a driving factor for tumour growth, expansion, formation of bone lesions and potentially also activation of disseminated tumour cells, leading to bone relapses. We review the current knowledge of bone targeted therapies in advanced breast cancer, with a focus on new insights into their bone-preserving and antitumor activity. Current guidelines, pathology of bone metastasis, mode of action and common side effects have been summarised. We also elaborate on the use of bisphosphonates and denosumab in early breast cancer, during adjuvant therapy with aromatase inhibitors.